A Co(II)-mediated coordination polymer: treatment capability on post-traumatic osteoarthritis via reducing inflammatory response. Issue 1 (2nd January 2021) - Zhang, Xi-Biao; Jia, Zhi-Cai; Ma, Hao-Guang; Pan, Hua; Lin, Xiang-Bo; Zeng, Haibo
Abstract: By using a mixed-ligand approach, a new Co(II)-mediated coordination polymer (CP) with the chemical formula of {[Co(L)(ipa)]·EtOH}n (1 ) has been successfully prepared by reaction of Co(OAc)2 ·4H2 O with isophthalic acid (H2 ipa) as well as the N-donor ligand 1, 3-bis(benzimidazol-1-yl)-2-propanol (L) under the solvothermal reaction condition. Furthermore, the nano-sheet of compound 1 was prepared by grinding method, which has good water-dispersion. The in vivo protective effect of nano 1 was evaluated on post-traumatic osteoarthritis (OA) model. First of all, the Enzyme-linked immunoblotting (ELISA) detection was performed to detect the content of the inflammatory cytokines in OA rats. Next, the relative expression levels of caspase-1, nlrp3 as well as il-1β inflammatory cytokine genes were measured with real-time Reverse Transcription Polymerase Chain Reaction (RT-PCR). The potential binding mode of the compound and the NLRP3 was predicted by performing computational docking and pose scoring process, indicating a possible binding site of the compound on NLRP3.